Fast Fashion In Indonesia: The Influence Of Negative Knowledge, Materialistic Motivation And Responsibility Ascription On Consumer Purchase Intention - Tria Mir’atul Mukaromah; Erlita Ridanasti (UNIVED Press, 2025)
The emergence of fast fashion in the global fashion industry has changed consumer consumption patterns. However, unsustainable fast fashion consumption patterns carry risks to environmental and social sustainability. Indonesia, as the fourth most populous country in the world, has many consumers who use fashion products, including fast fashion. However, fashion orientation factors and consumer intentions always lead to certain behaviors. This study aims to examine the factors that influence Indonesian consumer behavior towards their choice of fashion products. . Four hypotheses based on the theory of the influence of negative knowledge of fast fashion, materialistic motivation and ascription of responsibility on fast fashion purchase intentions in Indonesia. The study was conducted to form a hypothesis system, as many as 131 valid questionnaires were collected by random sampling in several cities in Indonesia. Data analysis and hypothesis testing were carried out using SEM Amos statistical software. The results of the study indicate that Indonesian consumer behavior towards fast fashion products tends to be positively influenced by negative knowledge of fast fashion. Then there is a positive correlation between Materialistic motivation and Consumer Attitude. There is a positive correlation between Ascription of responsibility and Consumer Attitudes. There is a positive correlation between Consumer Attitudes and Purchase Intention.